Total synthesis of (R)-lipoic acid and (S)-lipoic acid via an Mn (III)-salen-catalyzed oxidative kinetic resolution - Purude, Abhijeet N.; Pawar, Kailash P.; Patil, Niteen B.; Kalkote, Uttam R.; Chavan, Subhash P. (Tetrahedron-Asymmetry, 2015)
The asymmetric synthesis of both the antipodes of alpha-lipoic acid is described. The total synthesis of racemic and asymmetric lipoic acid is achieved from propane 1,3-diol. This work reports the use of Mn (III)-salen-catalyzed oxidative kinetic resolution as the key step to obtain enantiomerically pure (R)- and (S)-lipoic acid. The undesired product formed during the resolution can be recycled to achieve the desired isomer. (C) 2015 Elsevier Ltd. All rights reserved.